2011
DOI: 10.5301/ejo.2010.6049
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Retinal Barrier

Abstract: The blood-ocular barrier system is formed by 2 main barriers: the blood-aqueous barrier and the blood-retinal barrier (BRB). The BRB is particularly tight and restrictive and is a physiologic barrier that regulates ion, protein, and water flux into and out of the retina. The BRB consists of inner and outer components, the inner BRB being formed of tight junctions between retinal capillary endothelial cells and the outer BRB of tight junctions between retinal pigment epithelial cells. The BRB is essential to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
277
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 400 publications
(288 citation statements)
references
References 14 publications
1
277
0
10
Order By: Relevance
“…This is in agreement with prior evidence from trials of ruboxistaurin, an orally administered inhibitor of protein kinase C-β, in DME patients, which showed that the most probable cause of sustained moderate vision loss in the eyes in their study was the presence of increased retinal thickening involving the center of the macula [11,12]. It is generally accepted that, in the initial stages of clinical DR, increased retinal thickness is associated with an early alteration of the inner blood-retinal barrier [13,14]. The resultant accumulation of fluid in the retinal layers around the fovea may lead to vision loss by altering the functional cell relationship in the retina and/or by promoting an inflammatory reparative response [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with prior evidence from trials of ruboxistaurin, an orally administered inhibitor of protein kinase C-β, in DME patients, which showed that the most probable cause of sustained moderate vision loss in the eyes in their study was the presence of increased retinal thickening involving the center of the macula [11,12]. It is generally accepted that, in the initial stages of clinical DR, increased retinal thickness is associated with an early alteration of the inner blood-retinal barrier [13,14]. The resultant accumulation of fluid in the retinal layers around the fovea may lead to vision loss by altering the functional cell relationship in the retina and/or by promoting an inflammatory reparative response [14].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that, in the initial stages of clinical DR, increased retinal thickness is associated with an early alteration of the inner blood-retinal barrier [13,14]. The resultant accumulation of fluid in the retinal layers around the fovea may lead to vision loss by altering the functional cell relationship in the retina and/or by promoting an inflammatory reparative response [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased RT in diabetes, in the initial stages of clinical DR, has been associated with the presence of an early alteration of the inner blood-retina barrier and resultant fluid accumulation in the retina [38]. There have also been reports of retinal ganglion cell death and axonal degeneration occurring in the initial stages of DR, particularly in diabetes type 1 patients [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The inner BRB is formed by tight junctions between retinal capillary endothelial cells, and its integrity is maintained by adhesive interactions between endothelial cells and associated pericytes 8,9 . The outer BRB consists of the retinal pigment epithelium cells, located between the fenestrated choriocapillaris and the outer retina 10 .…”
Section: Blood-retinal Barriermentioning
confidence: 99%